Historiographical Analysis of Educational Activities of P.Kapteryev before 1917 - Larysa Herasymenko (Pedagogical Discourse, 2013)
The historiographical analysis of pedagogical legacy of P.Kapteryev of prerevolutionary period has been offered in the article. The main directions of scientific activity of the outstanding scientist: didactics, pedagogical psychology, family pedagogy, history of pedagogy have been studied. Little-known reviews of his public speeches have been analyzed, reviews of the works, published during the lifetime of the outstanding teacher have been studied, thus forming an objective view of his personality and teaching activities in the context of development of pedagogics and educational process of the second half of the XIX – beginning of the XX  century.